Physiological demands of downhill mountain biking - Burr, J. F.; Drury, C. T.; Ivey, A. C.; Warburton, D. E. R. (Journal of Sports Sciences, 2012)
Mountain biking is a popular recreational pursuit and the physiological demands of cross-country style riding have been well documented. However, little is known regarding the growing discipline of gravity-assisted downhill cycling. We characterised the physiological demands of downhill mountain biking under typical riding conditions. Riding oxygen consumption (VO2) and heart rate (HR) were measured on 11 male and eight female experienced downhill cyclists and compared with data during a standardised incremental to maximum (VO2max) exercise test. The mean VO2 while riding was 23.1 ± 6.9 ml/kg·min or 52 ± 14% of VO2max with corresponding heart rates of 146 ± 11 bpm (80 ± 6% HRmax). Over 65% of the ride was in a zone at or above an intensity level associated with improvements in health-related fitness. However, the participants` heart rates and ratings of perceived exertion were artificially inflated in comparison with the actual metabolic demands of the downhill ride. Substantial muscular fatigue was evident in grip strength, which decreased 5.4 ± 9.4 kg (5.5 ± 11.2%, P = 0.03) post-ride. Participation in downhill mountain biking is associated with significant physiological demands, which are in a range associated with beneficial effects on health-related fitness.